2021
DOI: 10.2991/ijcis.d.210203.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparing performances and effectiveness of machine learning classifiers in detecting financial accounting fraud for Turkish SMEs

Abstract: Turkish small-and medium-sized enterprises (SMEs) are exposed to fraud risks and creditor banks are facing big challenges to deal with financial accounting fraud. This study explores effectiveness of machine learning classifiers in detecting financial accounting fraud assessing financial statements of 341 Turkish SMEs from 2013 to 2017. The data are obtained from one of the leading creditor banks of Turkey. Highly imbalanced classes of 1384 nonfraudulent cases and 321 fraudulent cases (by 122 firms) are detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…Besides, the limited audit process period becomes an obstacle in the audit process [20]. A study [21,22] shows that clients can use the auditor switching mechanism to reduce the possibility of observe fraud in the company's financial statements.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, the limited audit process period becomes an obstacle in the audit process [20]. A study [21,22] shows that clients can use the auditor switching mechanism to reduce the possibility of observe fraud in the company's financial statements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…New auditors need a lot of time to study the company's characteristics in the audit process, so they are not able to know in detail the potential for fraud of the company. The research of [21] revealed that audit failure increased due to the change of auditors in the company. Study [18,20,37,38] shows that clients can use the auditor switching mechanism to reduce the prospect of detecting fraudulent acts in the company's financial reporting.…”
Section: Research Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional approaches to the detection of financial statement fraud are regression analysis, discriminant analysis, cluster analysis, and factor analysis. Hamal and Senvar [34] suggest that the detection of financial statement fraud requires sophisticated analytical tools and techniques, rather than the traditional methods adopted by decision-makers like auditors. However, there is no one-size-fits-all method for the detection of financial statement fraud according to the literature.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, data mining and machine learning techniques do not need the presumptions required by traditional statistics and can effectively handle non-linear problems [9]. For example, methods such as Artificial Neural Network (ANN), Support Vector Machine (SVM), Decision Tree (DT), and Bayesian Belief Network (BBN) are being used to detect financial statement fraud [7,8,10,28,32,34,38,40,41]. In the era of artificial intelligence, deep learning techniques are used by studies for the detection of financial statement fraud [35,42].…”
Section: Related Workmentioning
confidence: 99%